Text Summarization for Psoriasis of Text Extracted from Online Health Forums using TextRank Algorithm - Balipa, Mamatha; Balasubramani R, Dr; Vaz, Harolin; Shilpa Jathanna, Christina (International Journal of Engineering and Technology, 2026)
Text summarization is a process by which a document with enormous text and information is condensed into a summary of fewer sentences. In other words, it’s a technique employed to extract significant contents from a text document, so that it can be represented in a summary.In recent years, this technique has seen a tremendous importance in various fields including search engine, business analysis, market review, medical applications etc. In this paper we have attempted to implement automatic text summarization for summarizing information from online health care forums about the disease Psoriasis.
Keywords: Text summarization; TextRank algorithm; summary